A novel, low-cost clay ceramic membrane for the separation of oil-water emulsions - Dema Almasri; Yehia Manawi; Suhde Makki; Nafia Tasneem; Simjo Simson; Iman Abdel-Hadi; John Agcaoili; Jenny Lawler; Viktor Kochkodan (Scientific Reports)
Abstract The development of a facile and efficient method for the fabrication of ceramic membranes fills a vital gap in the ceramic membrane manufacture research field. Ceramic membranes are relatively high in cost due to the cost of raw materials (metal oxides) as well as the energy required during the sintering stage of the fabrication process. In this study, a ceramic membrane made of low-cost halloysite nanotubular (HNT) clay is fabricated through a die press process and sintered at temperatures notably lower than those required of raw materials in commercial membranes. The features of the membrane were evaluated in terms of chemical properties, surface characteristics, hydrophilicity, durability, oil rejection performance, and antifouling properties. The pore size, porosity, and water permeability corresponding to the optimum membrane composition: halloysite: Al2O3: starch as 60:25:15 wt% were found to be 230 nm, 62.4%, and 1040 LMH/bar, respectively. The membrane demonstrated to be superhydrophilic in air and superoleophobic underwater. The performance tests were conducted with oil emulsions. Oil-water rejection tests were conducted at different concentrations of oil-in-water emulsions (724 and 1014 mg/L) and oil rejection was observed to reach more than 99%. The flux recovery ratio (FRR) of the membrane in the first filtration cycle when treating the lower oil concentration emulsion was 54% greater than the FRR corresponding to the higher oil concentration emulsion. However, in the next filtration cycle, the FRR of the ceramic membrane was 30% greater for the higher oil concentration emulsion which could be attributed to the formation of an oil film, preventing further oil particle penetration in the membrane matrix. The testing with real produced water from gas extraction indicated that the novel HNTs-based ceramic membrane performed well in feed solutions with high total dissolved solids content and can be used for produced water pretreatment before reverse osmosis membranes if the produced water to be desalted. The results from this work show that the developed ceramic membrane could be a promising, low-cost alternative to the ones existing in the current market for oily wastewater treatment.